Biodegradation of chlorothalonil by Enterobacter cloacae TUAH-1. (July 2017) - Tang, Liwei; Dong, Jianjiang; Ren, Liwei; Zhu, Qifa; Huang, Weiwei; Liu, Yongmin; Lu, Diannan
Abstract: The long-term excessive use of chlorothalonil (CTN) can lead to serious environmental pollution, which presents a cause for concern. Here, we investigated the degradation of CTN by using an effective strain, TUAH-1, which was identified as Enterobacter cloacae according to the morphological approach, 16S rDNA gene sequence and phylogenetic tree analysis. Treatment with TUAH-1 demonstrated that the maximum processing capability was 74 mg CTN per gram dry cells in 48 h under optimum conditions (30 °C–35 °C, pH 7.0). After treatment with 21.3 mg dry cells, the degradation efficiency was 97.4% for 20 mg l -1 CTN in the aqueous phase. Meanwhile, treatment with crude enzyme solution containing 2.0 mg ml -1 protein led to complete degradation of 20.0 mg l -1 CTN within 10 h, which is significantly faster than that of TUAH-1. The results also showed that CTN could not be detected after treatment with 5.68 g TUAH-1 per kg soil for 48 h when the original CTN content in the soil was 10 mg kg -1 . After treatment with THAH-1 or its crude proteins, many degradation products were detected by HPLC-MS, suggesting two possible degradation pathways. The mechanism of CTN degradation by TUAH-1 was noted to be multienzymatic catalysis comprising glyceraldehyde-3-phosphate dehydrogenase and glutathione S-transferase. Highlights: Both TUAH-1 cell and its crude enzymes have capacity of CTN degradation in both aqueous and soil. After treatment with 21.3 mg dry cells, the degradation efficiency was 97.4% for 20 mg L -1 CTN in the aqueous phase. Treatment with crude enzyme solution containing 2.0 mg mL -1 protein led to complete degradation of 20.0 mg L -1 CTN within 10 h, which is significantly faster than that of TUAH-1. According to degradation products detected by HPLC-MS, degradation pathways of CTN by TUAH-1 were proposed. The mechanism of CTN degradation by TUAH-1 is multi-enzymatic catalysis.